Experimental methods in chemical engineering: Hazard and operability analysis—HAZOP. (9th August 2022) - Mocellin, Paolo; De Tommaso, Jacopo; Vianello, Chiara; Maschio, Giuseppe; Saulnier‐Bellemare, Thomas; Virla, Luis D.; Patience, Gregory S.
Abstract: Hazards and operability analysis (HAZOP) is one of a dozen‐structured Process Hazards Analysis (PHA) methodologies that assess risks associated with operating processes to mitigate their consequences. HAZOP applies to all six stages of process design from discovery to decommissioning. Industry massively adopted PHA methodologies as a consequence of several industrial disasters in the 1970s that increased society's scrutiny of chemical operations. HAZOPs are conducted by multidisciplinary teams that rely on a set of guide words in combination with the system parameters to identify deviations from the design intent. The team discuss the causes and consequences of deviations, and the project owner modifies the process accordingly. It relies on heuristics rather than algorithms, so the formal structure gives practitioners the false sense that the analysis is comprehensive. Academic institutions increasingly apply PHAs to experimental work, but the scope of a HAZOP is often ill‐suited for this environment as it requires dedicated personnel with particular expertise. Here, we outline the essential features of a HAZOP analysis for early career researchers engaging in process development for conditions that include, for example, high temperature, high pressure, toxic compounds (Hg, phosgene, CO), and potentially explosive and flammable mixtures like organic peroxides. Web of Science indexed over 100 000 documents that mention safety in 2021 and assigned 1500 to chemical engineering. A bibliometric analysis grouped them into five clusters: (1) lithium ion batteries and nanoparticles, (2) fire, simulation, and combustion, (3) models, risk, systems, and techniques (including HAZOP), (4) water treatment, and (5) mechanisms and thermal runaway. [Correction added on 01 September 2022, after first online publication: The item number 3 in the preceding sentence was duplicated in the original published article and has been deleted in this version.]